Understanding the open education approach and OERs characteristics - Morgado, Lina (2015)
The Unit 1 is part of the training material "OER and Sustainability Models" to train trainers) and it is organised in Units. Inn the Unit 1, the learner will be able to: i) understand the approach of open movement; ii) describe/identify specific characteristics of OER; iii) find, select and use/reuse/make one OER; iii) analyse case studies of sustainable models of OERThis Unit focuses on understanding the approach of the open education movement. Having successfully completed this Unit, the learner will be able to: a) understand the open education movement; b) describe/identify specific characteristics of OER. The content is an OER.